Screening and Response to Maternal Mental Health Problems. Issue 5 (September 2017) - Wisner, Kirsten
Abstract : Our maternity nursing expert, Kirsten Wisner, provides details about the new consensus bundle on maternal mental health from the Council on Patient Safety in Women's Health Care.